Engineering the Ionic Polymer Phase Surface Properties of a PEM Fuel Cell Catalyst Layer. Issue 2 (1st January 2017) - Dowd, Regis P.; Day, Cynthia S.; Van Nguyen, Trung
Abstract : During high power density operations, the performance of polymer electrolyte membrane fuel cells (PEMFCs) may be limited by high water saturation levels in the cathode catalyst layer due to high wettability of the ionic polymer phase. A new heat-treatment method was used to create and lock-in the surface structure of Nafion 212. Several surface characterization techniques were used to verify the membrane's surface after heat-treatment, including contact angle, atomic force microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. We found that specific heat-treatment conditions led to the formation of either a hydrophobic or hydrophilic surface. The modified membrane's surface remained intact even after the membranes were boiled in water for 1 h. Next, a 4-point conductivity technique was used to verify that the heat-treatment conditions which led to a hydrophobic surface did not negatively impact the membrane's internal conductivity. Finally, this novel heat-treatment method was applied to the cathode catalyst layer of a H2 -Air PEMFC to create a hydrophobic polymer-gas interface inside the gas pores of the cathode catalyst layer. Preliminary results showed 33% increase in peak power. The results of this research will guide the design of a new class of PEMFC catalyst layers.